The geological and tourist attractions of the largest Australian cities and their surroundings - Jamorska, Izabela (Geotourism/Geoturystyka, 2017)
Australia, labelled the continent of contrasts, is one of the most geologically interesting places in the world. Australia is home to some of the oldest rocks and minerals in the world. Some of the oldest parts of Australia are incredibly well preserved, with rocks that appear as though they could have formed yesterday. The majority of Australians live in coastal areas, because the interior of the country, called the Outback can be a very arid area with many deserts and a lack of water. The largest cities, like Sydney, Perth and Melbourne, are situated along the coast. Great distances between the cities are surprising to foreigners. In these areas, buildings or people are not the most interesting attractions. In fact, it is the geology that is most interesting.